Rhodium‐Catalyzed Asymmetric Cycloisomerization and Parallel Kinetic Resolution of Racemic Oxabicycles. (15th July 2016) - Loh, Charles C. J.; Schmid, Matthias; Webster, Robert; Yen, Andy; Yazdi, Shabnam K.; Franke, Patrick T.; Lautens, Mark
Abstract: While desymmetrizations by intermolecular asymmetric ring‐opening reactions of oxabicyclic alkenes with various nucleophiles have been reported over the past two decades, the demonstration of an intramolecular variant is unknown. Reported herein is the first rhodium‐catalyzed asymmetric cycloisomerization of meso ‐oxabicyclic alkenes tethered to bridgehead nucleophiles, thus providing access to tricyclic scaffolds through a myriad of enantioselective C−O, C−N, and C−C bond formations. Moreover, we also demonstrate a unique parallel kinetic resolution, whereby racemic oxabicycles bearing two different bridgehead nucleophiles can be resolved enantioselectively.